A training model for progress in curriculum greening - Bonil, Josep; Calafell, Genina; Granados, Jesús; Junyent, Mercè; Tarín, Rosa Maria (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
It is presented a qualitative research that aims to provide answers to the shared diagnosis of the lack of training of educative teams concerning Curriculum Greening. We present a training model that has been implemented in a training activity addressed to teachers from primary and secondary education, and also to consultants of Environmental Education who belong to the Xarxa d’Escoles per a la Sostenibilitat de Catalunya (Network of Schools for the Sustainability of Catalonia). The purpose of the model is to shorten the distance between the ideological approach of Environmental Education and its practical concretion in the classroom, which often becomes an obstacle to Curriculum Greening. To this end, the training proposal is based on the concept of high level idea and its connection with the practice, that has been specified in the identification of four spheres: conceptual, creative, didactic and research. The work presented concludes that the proposed model is a coherent, solid and rigorous way of approaching Curriculum Greening. Furthermore, the study has enabled to identify, between the teachers who participated in the training activity, four profiles depending on the grade of transference of the model to their professional context: propellant, catalyst, cognitive reinforcement and emotional reinforcement. This categorization offers elements that enable to explore which components, in both teaching and consultant level, should be considered and which should be surpassed to achieve a high level of transference of the training proposal in order to improve the level of Curriculum Greening.